2020
DOI: 10.11591/ijere.v9i1.20455
|View full text |Cite
|
Sign up to set email alerts
|

Why some religious individuals are not emotionally smart? The explanatory role of spirituality

Abstract: <p align="left">In two studies, we intend to investigate whether spirituality can explain the relationship between intrinsic religious orientation (IRO) and emotional intelligence (EI). Seventy-three worshipping houses-going adults, aged 18-56, had participated in the study. Data was collected by employing Intrinsic Scale of Religious Orientation Scale, Spirituality Assessment Scale, and the Schutte Self-Report Emotional Intelligence Test. Our first study discovered that IRO is not a significant predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 53 publications
(78 reference statements)
2
10
0
Order By: Relevance
“…In line with that, Miguel-Rojas et al [55] suggested that spirituality is positively correlated with a positive understanding that others have sympathy and empathy towards oneself, which led to the sense of receiving support from others. Consistent with that, our previous study in the Malaysian context before the MCO suggested that spirituality significantly predicts one of the preconditions of PSS, which is emotional intelligence [56] and some previous studies also confirmed that spirituality predicts another precondition, social-connectedness [53], [54]. Accordingly, various studies from various settings reported a positive link between spirituality and PSS, such as among university students in Jordan [48], women with preeclampsia [57], burn survivors in Iran [58], African American women with breast cancer [59].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with that, Miguel-Rojas et al [55] suggested that spirituality is positively correlated with a positive understanding that others have sympathy and empathy towards oneself, which led to the sense of receiving support from others. Consistent with that, our previous study in the Malaysian context before the MCO suggested that spirituality significantly predicts one of the preconditions of PSS, which is emotional intelligence [56] and some previous studies also confirmed that spirituality predicts another precondition, social-connectedness [53], [54]. Accordingly, various studies from various settings reported a positive link between spirituality and PSS, such as among university students in Jordan [48], women with preeclampsia [57], burn survivors in Iran [58], African American women with breast cancer [59].…”
Section: Introductionsupporting
confidence: 85%
“…Different professions might require different degrees of adjustment when practised from home, and therefore they might produce different social dynamics; in other words, the degree of adjustment to work from home (WFH) might play a moderation role 299 in the equation. The second methodological limitation is that we did not take into account of the separation between intrinsic and extrinsic spirituality, as suggested in the study of Ng and Prihadi [56]. It was questionable that our findings were not consistent with the recent studies that spirituality predicted SWL [50], PSS [56] and resilience [45].…”
Section: Limitationmentioning
confidence: 72%
See 1 more Smart Citation
“…These are circulated in applications for business, but they also apply to educational and literacy research (e.g. Toosi et al, 2016;Ng & Prihadi, 2020). The key point for the present study, though, is that it is not necessarily expected that university students in Malaysia or elsewhere would relate these meta-functions to their conceptions of 'language', and it may be even less expected that when they give metaphors for 'language' or 'learning' they might share conceptualizations which indicate these meta-functions.…”
Section: Language and Meta-functions In Educationmentioning
confidence: 99%
“…Another visible challenge in our studied community was the ingroup-outgroup prejudice tendency among the members of rural communities with different belief system, such as reported in Malaysia [21] and in Thailand [22], that individuals from certain belief system would not comply to leaders from different belief systems. Ng and Prihadi [23] explained that while religions of any kind promote peaceful social interactions, the excessive levels of extrinsic spirituality might lead people into lower emotional intelligence; where they would likely to take the superficial meanings of religious activities as being exclusive and that others are considered less holier, therefore, should not be tolerated. While the latter study suggested that when individuals approach their belief system through intrinsic spirituality mechanism, they would put higher values in their relationship with the divine power, as well as with other members of the society, the former two studies indicated that extrinsic spirituality approach is dominant in rural areas of South East Asia, and therefore might hinder any attempt for interfaith leadership.…”
Section: Introductionmentioning
confidence: 99%